Tim-1 Deficiency Aggravates High-Fat Diet-Induced Steatohepatitis in Mice - George, Jasmine; Zhang, Yuanyuan; Sloan, Jacob; Sims, Joya M.; Imig, John D.; Zhao, Xueying (Frontiers in Immunology, 2021)
Non-alcoholic fatty liver disease (NAFLD)/non-alcoholic steatohepatitis (NASH) is commonly associated with obesity and characterized by excessive lipid accumulation and liver inflammation. The T cell immunoglobulin and mucin domain 1 (Tim-1), also known as hepatitis A virus cellular receptor 1 (Havcr-1) and kidney injury molecule 1 (Kim-1), has been shown to affect innate immunity-driven proinflammatory cascade in liver ischemia-reperfusion injury. However, its contribution to obesity-related NAFLD/NASH remains unknown. Thus, this study was designed to evaluate the role of Tim-1 in obesity-related liver inflammation and injury in wild-type (WT) and Tim-1-deficient (Tim-1-/-) C57BL/6J mice fed a high-fat diet (HFD) for 5-6 months. HFD feeding induced steatosis and upregulated Tim-1 gene expression in the liver of WT mice. Surprisingly, Tim-1-/- mice on HFD diet exhibited an exacerbation of hepatic steatosis, accompanied with an elevation of protein levels of fatty acid translocase CD36 and sterol regulatory element binding protein 1 (SREBP1). Tim-1 deficiency also enhanced HFD-induced liver inflammation and injury, as evidenced by augmented increase in hepatic expression of pro-inflammatory factor lipocalin 2 and elevated serum alanine transaminase (ALT). In addition, gene expression of type I, III and IV collagens and liver fibrosis were greatly enhanced in HFD Tim-1-/- mice compared with HFD WT mice. HFD-induced hepatic expression of YM-1, a specific mouse M2 macrophage marker, was further upregulated by deletion of Tim-1. Together, these results show that Tim-1 deficiency aggravates the effects of HFD diet on lipid accumulation and liver fibrosis, most likely through enhanced infiltration and activation of inflammatory cells.